Rooting of blueberry seedlings under ex vitro conditions and different substrates Enraizamento de plântulas de mirtileiro em condição ex vitro com diferentes substratos - Pelizza T.R.* (2012)
The objective of this study was to measure the capacity of ex vitro rooting of blueberry seedlings cultivars Bluebelle, Woodard and Georgiagem under different substrates. The experiment was carried out from February to April, 2009 in greenhouse at ± 25°C, set at Universidade Federal de Pelotas (UFPel/FAEM) in Pelotas (RS). The seedlings (seven buds and seven leaves + stem apex) were immersed in IBA for 10 minutes, and after were put in closed plastic trails filled up with the following substrates: a) Plantmax®, b) Plantmax® + old pine sawdust (totally degraded), c) old pine sawdust, d) Plantmax® + medium grade expanded vermiculite and e) medium grade expanded vermiculite. The experimental design was completely randomized in a 3×5 factorial arrangement, with three cultivars and five substrates. There were four replications per treatment and eight seedlings per replication. After 75 days the percentage of rooting seedlings, callus formation, surviving seedlings, length and number of roots, length of the largest root, seedlings height, number of shoots and total fresh biomass were assessed. The better substrates to ex vitro rooting of blueberry seedlings are medium grade expanded vermiculite, old pine sawdust and Plantmax® + medium grade expanded vermiculite. Higher potential of ex vitro rooting is achieved with the cultivars Bluebelle and Woodard.